Construction of Interface Dipoles by Surface Doping and Their Role in the Open Circuit Voltage in Polymer Solar Cells - Li, Shiyu; Wen, Xinbo; Zhou, Jiadong; Zheng, Nan; Liu, Linlin; Xie, Zengqi (Organic Materials, 2020)
A kind of dipolar interface is realized by surface doping of poly-(3,4-ethylenedioxythiophene) (PEDOT) with tetrafluoro-tetracyano-quinodimethane (F4TCNQ). PEDOT is in situ synthesized by electrochemical polymerization of 3,4-ethylenedioxythiophene (EDOT) on an indium tin oxide (ITO) electrode, and then F4TCNQ is spin-coated atop the PEDOT layer. Because the LUMO of F4TCNQ is lower than the HOMO of PEDOT, the spontaneous electron transfer from PEDOT to F4TCNQ results in a bilayered structure of PEDOT cations and F4TCNQ anions. Thus, a permanent interfacial dipole is formed in the surface-doping system. The surface doping not only enhances the conductivity of PEDOT, but also increases the surface work function of the electrode. The dipolar film is applied as the anode interface in polymer solar cells (PSCs), and the results show that such an interface dipole plays a very important role in the open circuit voltage (Voc) of the PSCs.
Keywords: interfaces; charge transfer; dipoles; solar cells; surface doping